THE MASTER'S THESIS. - Miller, H. C. (The Accounting Review, 1935)
Through the cooperation of some of the members of the accounting association a list of accounting theses for a master's degree has been compiled. Requests for titles approved during the past five years were sent to 46 universities represented in The American Association of Collegiate Schools of Business. Thirty-eight answers were received. Ten of those replying indicated that no graduate work in accounting, as a major field, has been done. Four more indicated that the thesis requirement has been abolished or waived. Twenty-four replies listed titles numbering more than 415, but the excess over that number represented subjects approved prior to 1919, doctors' dissertations, or bachelors' honors reports. Elementary, intermediate, and advanced or special courses such as cost accounting, auditing, income tax, budgeting, accounting systems and problem review must be made a part of the equipment of the graduate accounting student who would carry on research in his chosen field. Probably nothing, which the average graduate student must do is as difficult for him as the selection and statement of his thesis subject.